Magnoflorine Suppresses MAPK and NF-κB Signaling to Prevent Inflammatory Osteolysis Induced by Titanium Particles In Vivo and Osteoclastogenesis via RANKL In Vitro - Sun, Zhenyu; Zeng, Junkai; Wang, Wenjuan; Jia, Xinlin; Wu, Qiang; Yu, Degang; Mao, Yuanqing (Frontiers in Pharmacology, 2020)
Wear particles that detach from the surface of prostheses induce excessive activation of osteoclast and immoderate release of inflammatory cytokines that lead to peri-implant osteolysis and aseptic loosening. In this work, we investigated whether magnoflorine, a quaternary aporphine alkaloid extracted from the Chinese herb Magnolia or Aristolochia, could effectively inhibit inflammatory calvarial osteolysis caused by titanium particles in mouse models, inflammatory response as well as osteoclastogenesis in vitro mediated via receptor activator of NF-κB ligand (RANKL). Micro-computed tomography and histological examination of mice treated with magnoflorine revealed fewer resorption pits, less osteoclasts formation and inflammatory cytokine expression. Moreover, in vitro differentiation of osteoclasts and bone resorption as well as titanium particle-induced inflammatory response were dose-dependently inhibited by magnoflorine. These were accompanied by reduced transcription of osteoclast-specific genes encoding tartrate-resistant acid phosphatase (TRAP), V-ATPase d2, c-Fos, cathepsin K, nuclear factor of activated T cells (NFAT) c1, and calcitonin receptor (CTR). Further research on mechanism showed that the inhibition of phosphorylation of TAK1 and subsequent activation of MAPK and NF-κB signaling pathways were found to mediate the suppressive effects of magnoflorine. Collectively, these results suggested that magnoflorine treatment could effectively prevent peri-implant osteolysis due to wear debris as well as other diseases caused by chronic inflammation and excessive osteoclast activation.